432 – Correlation between regional brain volume and olfactory function in very mild amnestic patients. (October 2020) - Kashibayashi, Tetsuo
Abstract : Background & Aims: We aimed to determine neural correlates of olfactory detection and identification and analyze associations between cognitive function and olfactory identification or detection in very mild amnestic patients. Methods: We recruited 70 patients with chief complaints of memory impairment diagnosed as amnestic mild cognitive impairment (MCI) or Alzheimer's disease (AD) with a clinical dementia rating of 0.5. Olfactory detection and identification were assessed using T&T olfactometry. A voxel-wise correlation analysis of gray matter volume and olfactometry scores was performed. We also analyzed correlations between neuropsychological results and olfactometry scores. Results: A significant negative correlation was observed between detection scores and nucleus accumbens and left parahippocampal gyrus volumes and between identification scores and orbitofrontal, right frontal, and right anterior temporal cortex volumes (p<0.001). No significant correlation existed between detection and cognitive assessment scores. Identification score was significantly correlated with the Alzheimer's Disease Assessment Scale-Cognitive Part word recall score (r=0.305, p=0.01). Conclusions: Olfactory detection and identification dysfunction were attributable to impairments in different regions in MCI and very early AD; the former was attributed to the olfactory circuit, while the latter to neocortices. The dysfunction of identification of olfactory information was associated with episodic memory in those patients.